Nobiletin Inhibits IL-1β-Induced Inflammation in Chondrocytes via Suppression of NF-κB Signaling and Attenuates Osteoarthritis in Mice - Lin, Zeng; Wu, Dengying; Huang, Lipeng; Jiang, Chao; Pan, Tianlong; Kang, Xiaodiao; Pan, Jun (Frontiers in Pharmacology, 2019)
Osteoarthritis (OA), a common degenerative joint disease, is principally characterized by inflammation and destruction of cartilage. Nobiletin, an extract of the peel of citrus fruits, is known to have anti-inflammatory properties. However, the mechanisms by which nobiletin plays a protective role in osteoarthritis (OA) are not completely understood. In the present study, we investigated the anti-inflammatory effects of nobiletin in the progression of OA in both in vitro and in vivo experiments. Mouse chondrocytes were pretreated with nobiletin (0, 10, 20, 40 μM) for 24 h and then incubated with IL-1β (10 ng/mL，24 h) in vitro. The generation of PGE2 and NO were evaluated by the Griess reaction and ELISAs. The protein expression of inducible nitric oxide synthase, matrix metalloproteinase-3, matrix metalloproteinase-13, A disintegrin and metalloproteinase with thrombospondin motifs-5 (ADAMTS5), cyclooxygenase-2, collagen II and aggrecan were analyzed by Western blotting. Immunofluorescence and Western blot analysis were used to detect nuclear factor-κB (NF-κB) signaling molecules. Induction of proinflammatory and catabolic mediators by IL-1β stimulation of mouse chondrocytes could be partially blocked by treatment with nobiletin or ammonium pyrrolidine dithiocarbamate (an NF-kB inhibitor). Furthermore, our results indicated that nobiletin exhibited a therapeutic effect through active inhibition of the NF-κB signaling pathway. In a mouse model of OA, injection of nobiletin (20 mg/kg) every 2 days for 8 weeks after surgery inhibited cartilage destruction and synovitis. Taken together, our findings suggest that nobiletin may be a potential therapeutic agent for the treatment of OA.